Pemberdayaan Masyarakat Desa Borisallo Akan Pemanfaatan dan Pengolahan Limbah Bulu Ayam Menjadi Material Panel Dinding - Ansarullah Faharuddin; Muhammad Zainal Altim; Siti Aisyah; Zulkarnain Hamson (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2023)
This PKM aims to, (1) provide residents with a solution for chicken feather waste which has not been utilized so far, to be managed and used as wall material, in order to increase knowledge, skills and mastery of technology in the use of chicken feather waste into panel material. (2) training and assistance to improve skills and additional income for residents in the application of feather panels for village office room dividers to improve services to the community. The method used is material engineering by processing chicken feather waste into wall panel material to increase residents' skills and resources in the ability to process waste into wall products for making room dividers in village offices in order to improve citizen services, this is in accordance with government programs related to focus. Indonesia's sustainable development, namely the Green economy.